2008
DOI: 10.1063/1.2965799
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric, electrical and magnetic properties of Cr, Mn, Co, Ni, Cu added polycrystalline BiFeO3 films

Abstract: Cr, Mn, Co, Ni, and Cu were added to polycrystalline BiFeO3 films, and their influence on the ferroelectric, electrical, and magnetic properties was investigated. All the additives except Ni reduced the leakage current density in the high electric field region. The addition of Cu and Co decreased the coercive field without reducing remanent polarization. The addition of Co caused spontaneous magnetization at room temperature, which exhibited a large coercive field of 16kOe at 10K. It was revealed that Co addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
105
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(113 citation statements)
references
References 13 publications
6
105
2
Order By: Relevance
“…Although P r is still not saturated, E c tends to saturate at 1250 kV/cm. Since the observed electric field dependences of P r value are almost comparable with those of polycrystalline pure BFO film capacitors measured by low temperature or high-speed positive-up-negative-down measurements, 10,16 degradations of ferroelectric properties due to ion doping are almost nothing. Hence, it is concluded that ͑Mn, Ti͒ codoping in the BFO film is an effective technique leading to the excellent ferroelectric properties at RT without any serious degradations.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…Although P r is still not saturated, E c tends to saturate at 1250 kV/cm. Since the observed electric field dependences of P r value are almost comparable with those of polycrystalline pure BFO film capacitors measured by low temperature or high-speed positive-up-negative-down measurements, 10,16 degradations of ferroelectric properties due to ion doping are almost nothing. Hence, it is concluded that ͑Mn, Ti͒ codoping in the BFO film is an effective technique leading to the excellent ferroelectric properties at RT without any serious degradations.…”
mentioning
confidence: 58%
“…[4][5][6][7][8][9][10][11]15 The site-engineering technique is quite important from industrial aspects because this technique can be applied to most deposition methods. However, it is not easy to reduce the leakage current of BFO films by a single ion-doping method since the excess substitution causes an increase in leakage current in the films.…”
mentioning
confidence: 99%
“…Both Bi-and Fe-site substitutions with a variety of cations have been attempted in BFO thin film. [14][15][16][17][18][19][20][21] Nevertheless, ferroelectric and magnetic behaviors of the substituted BFO thin films have great discrepancy across many research reports. The (La, Mn) co-substituting has been proposed as a promising strategy to simultaneously optimize ferroelectric and ferromagnetic properties, [22][23][24] but the cosubstitution effects of La and Mn on BFO so far have only been examined in form of polycrystalline thin films with rather scattered physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Many research groups have reported that a site-engineering technique using various elements is effective to suppress the leakage current in BFO films. [11][12][13][14][15][16] We proposed (Nd,Mn)-codoped BFO (BNFM) and (Pr,Mn)-codoped BFO (BPFM), and succeeded in obtaining improved electrical properties. 14,[17][18] Recently, polarization-induced photovoltaic properties in BFO films have been reported.…”
Section: Introductionmentioning
confidence: 99%